Pengaruh Metode Pembelajaran Edutainment Melalui Permainan Miskin Terhadap Hasil Belajar Biologi - Nurhasanah, Siti (Gema Widyakarya bekerjasama dengan Persatuan Guru Republik Indonesia (PGRI) Daerah Khusus Ibukota Jakarta, 2018)
The purpose of the research is to know the difference of the students' learning outcomes of the class X biology subjects of SMAN 1 Kopo between using edutainment method through the poor game using the conventional method. The research method used to analyze is the quasi-experimental method, while hypothesis testing using the t-test for the average difference test, which had previously done the normality test using Chi-square test and homogeneity test using Fisher test. Based on the test of experimental class data normality by using Liliefors test formula obtained χ ^ 2count <χ ^ 2table (1,306 <11,070), whereas the control class χ ^ 2count <χ ^ 2table (1,297 <11,070), from the data, can be expressed both classes are normally distributed, whereas for homogeneity test obtained Fhitung <Ftabel (1.136 <1.858) is homogeneous. Based on the hypothesis test for the average difference class done by using t-test then got result tcount> t-table (2,681> 2,04 0), the hypothesis H0 is rejected and H1 is accepted. The result of the research findings can be concluded that there is the influence of the use of edutainment learning method through the poor game to the biology study result of the Invertebrate subject in the students of class X SMAN 1 Kopo-Serang.